Asuhan Kebidanan Komprehensif pada Ny. L Umur 24 Tahun dengan Anemia Sedang di Puskesmas Bantarkawung Kabupaten Brebes Tahun 2025 - Tri Mulyani; Hafsah Hafsah; Mupliha Mupliha (Jurnal Siti Rufaidah, 2025)
Background: Maternal mortality according to WHO (2024) is 287,000, in Indonesia (2024) 183/100,000 live births, in Central Java (2024) 3,149 live births, in Brebes (2024) there were 54 cases of maternal mortality. At Bantarkawung Community Health Center (2024), there were no maternal deaths. One of the causes of maternal mortality is postpartum hemorrhage. Postpartum hemorrhage can be caused by anemia in mothers during pregnancy. Objective: It is hoped that the researcher can provide comprehensive midwifery care for Mrs. L in accordance with midwifery service standards, covering pregnancy, childbirth, newborns, neonates, postpartum, and family planning, using the midwifery management approach according to Varney and SOAP. Research method: The method used is qualitative descriptive with a comprehensive case study approach. Findings: During the researcher's assistance with anemia cases, the researcher did not find issues that required further in-depth investigation, but there were some occurrences resulting from anemia, one of which was the mother experiencing retained placenta. From the assistance process conducted by the researcher, the midwifery findings have been applied comprehensively, from pregnancy stages to family planning, in accordance with midwifery service standards.